1987
DOI: 10.1128/jb.169.9.4163-4170.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of genes controlling synthesis and activation of 2,3-dihydroxybenzoic acid in production of enterobactin in Escherichia coli

Abstract: The Escherichia coli gene cluster encoding enzymatic activities responsible for the synthesis and activation of 2,3-dihydroxybenzoic acid in the formation of the catechol siderophore enterobactin was localized to a 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…To meet the specific genetic requirements of our mutagenesis strategy, a derivative of pSUP202 (Table 1) (37), pLG51, was created by restricting pSUP202 with EcoRI, filling in the cut ends with Klenow fragment, and recircularizing the plasmid; this procedure inactivated the chloramphenicol resistance marker of the parent plasmid. A 6.3-kb HindIII fragment of the B. japonicum genome containing the N-terminal portion of sucA was then subcloned from pMDH9.0 (Table 1) into the HindIII site of pLG51 to form pLG11 and transformed into E. coli MC4160 (27). The plasmid was then mutagenized with the transposon Tn10-miniKan, delivered via a lambda phage derivative (43).…”
Section: Methodsmentioning
confidence: 99%
“…To meet the specific genetic requirements of our mutagenesis strategy, a derivative of pSUP202 (Table 1) (37), pLG51, was created by restricting pSUP202 with EcoRI, filling in the cut ends with Klenow fragment, and recircularizing the plasmid; this procedure inactivated the chloramphenicol resistance marker of the parent plasmid. A 6.3-kb HindIII fragment of the B. japonicum genome containing the N-terminal portion of sucA was then subcloned from pMDH9.0 (Table 1) into the HindIII site of pLG51 to form pLG11 and transformed into E. coli MC4160 (27). The plasmid was then mutagenized with the transposon Tn10-miniKan, delivered via a lambda phage derivative (43).…”
Section: Methodsmentioning
confidence: 99%
“…Walsh and coworkers (39,40), Earhart and coworkers (41,42), and McIntosh and coworkers (43,44) have shown that enterobactin is synthesized from a fork in the aromatic amino acid pathway in a two-step process (40,41,45). Chorismic acid, an aromatic amino acid precursor, is converted into isochorismate, then into 2,3-dihydro-2,3-dihydroxybenzoate, and finally into 2,3-dihydroxybenzoic acid (DHB).…”
Section: Biosynthesis Of Enterobactinmentioning
confidence: 99%
“…(The AN462 genotype was reported to result from Mu-induced polarity, and it is now clear that the rightmost operon of the Ent gene cluster consists of the genes entCEB[G]A and is transcribed from left to right [14,20,27,30], but more recently Laird and Young [19] suggested that a Mu-induced deletion of entB [G]A was responsible for the AN462 characteristics. Some recent workers [27,28] have adopted the latter suggestion.) Weak genetic complementation of the AN462 EntG defect occurs with plasmids containing an approximately 700-bp fragment that includes portions of entB and entA (28).…”
mentioning
confidence: 98%
“…Some recent workers [27,28] have adopted the latter suggestion.) Weak genetic complementation of the AN462 EntG defect occurs with plasmids containing an approximately 700-bp fragment that includes portions of entB and entA (28). However, recent sequencing data show that no separate and distinct open reading frame that could correspond to entG exists between entB and entA (20,27 MATERIALS AND METHODS Bacteria, plasmids, and bacteriophages.…”
mentioning
confidence: 98%